1971
DOI: 10.1136/bmj.2.5754.138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroxyethylrutosides on Blood Oxygen Levels and Venous Insufficiency Symptoms in Varicose Veins

Abstract: SummaryOxygen levels (tension, saturation, and content) in blood from varicose leg veins were found to be significantly lower than those in blood from normal leg Paroven, the product used, is a mixture mainly of mono-, di-, tri-, and tetra-O-(3-hydroxyethyl) rutosides containing not less than 45% troxerutin, the approved name of the principle compound tri-O-(/3-hydroxyethyl) rutoside. Hydroxyethylrutosides have been reported to relieve leg symptoms associated with varicose veins (Fitzgerald, 1967;Allen, 1970… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In the sodium morrhuate model HR decreased the frequency of thrombosis although not significant (p=O.O7) if the animals were treated three days. An effect on the vessel wall can not be excluded, as assumption which is supported by some clinical results (18).…”
Section: Discussionmentioning
confidence: 88%
“…In the sodium morrhuate model HR decreased the frequency of thrombosis although not significant (p=O.O7) if the animals were treated three days. An effect on the vessel wall can not be excluded, as assumption which is supported by some clinical results (18).…”
Section: Discussionmentioning
confidence: 88%
“…However, findings from these studies have been inconsistent as some studies demonstrated a lower oxygen content in blood from varicose compared to non-varicose veins [19,20,21], whereas others showed no significant differences [22,23,24,25,26]. Paradoxically, some studies even reported higher oxygen content in blood of varicose than non-varicose veins [22,23,27,28,29].…”
Section: Measuring Luminal Blood Oxygenation In Varicose Veinsmentioning
confidence: 84%
“…These improvements in varicose vein oxygenation were also associated with symptomatic relief in this patient group [19]. However, the findings of this study should be interpreted with caution as patients were not randomized, neither patients nor clinicians were blinded, and the timing of venepuncture was not matched between the study groups.…”
Section: Hypoxia and Treatment Of Varicose Veinsmentioning
confidence: 94%
See 2 more Smart Citations